UPAYA PENINGKATAN STANDAR PELAYANAN MINIMUM (SPM) JALAN TOL DI INDONESIA - Rudy Hermawan Karsaman (Direktorat Bina Teknik Jalan dan Jembatan, 2009)
One of the aspects needed to ensure smooth, safe, comfort, and efficient operation of a toll road is related to service and operating systems. The Minimum Service Standard (MSS) has been a parameter adopted for measuring the performance of a toll road and its service to the toll road users. Basically, this MMS should be fulfilled as a guarantee provided to the toll road users, which consists of road condition, average traffic speed, accessibility, mobility, safety, and support units for handling emergency conditions and traffic accidents. To enhance the toll road service in Indonesia, the MMS needs to be increased. This could be done by reviewing the MSS parameters and their values currently applied. The expectations from this effort are a better quality of the toll road, both safety and comfort, and increase in the level of service and safety for the toll road users. This paper describes proposed aspects which could be considered to increase the MSS, in its parameters and the values of those parameters. Keywords : Toll Road, Minimum Service Standard, Operation System